Micropropagation of Pluchea sagittalis (Lam.) Cabrera - L.V. ROSSATO; T.S. CANTO-DOROW; F.T. NICOLOSO (Universidade Estadual Paulista, 2015)
ABSTRACT:The objective of this study was to develop an in vitro protocol for the micropropagation of Pluchea sagittalis (Lam.) Cabrera. Plants were regenerated in vitro from stem segments. The procedure employed includes: 1) surface sterilization of shoots by immersion in 70% ethanol for 10 s followed by 1.0% NaOCl for 10 min, and subsequent immersion in 0.05% HgCl2 for 3 min and two washes with sterile distilled water; 2) induction of root and shoot by culture on hormone-free Murashige and Skoog medium (MS); 3) acclimatization of 60 day-old-plantlets in soil under ex vitro conditions. Minimum contamination was observed for apical shoot explants (10%). However, independently of the explant position in the stem, all explants regenerated new shoots. Various successive cultivations from stem explants every 60 days during more than 1 year have been shown to be a suitable method to propagate P. sagittalis in vitro. Low salt concentration (25% of the normal concentration) in the medium promoted greater growth of plantlets because the plants had a higher number of roots and longer roots in such an environment. Our protocol for the micropropagation of P. sagittalis can be accomplished as a two-step procedure within a short period of time (two months) before transplanting.